Enhancing the quality of maternal and neonatal care by the Safe Childbirth Project in Al Shifa Hospital, Gaza occupied Palestinian territory (oPt): a descriptive retrospective study. (July 2021) - Abu Ward, Itimad; Jouda, Amani; Balousha, Suha; Egenberg, Signe; Al Masri, Naila; Blix, Ellen
Abstract: Background: The Safe Childbirth Project is a campaign, launched by WHO in 2012, to improve the quality of care for women and babies during childbirth by promoting evidence-based practice and a midwifery-led approach to care. It was intended to contribute towards achieving UN Sustainable Development Goal 3: ensure healthy lives and promote wellbeing for all at all ages. In September, 2015, the project was launched in the maternity ward of Dar Al-Shifa Hospital, Gaza City, to promote midwifery-led care for low-risk deliveries, with de-medicalisation of normal birth, early initiation of breastfeeding, and early detection of complications during the postpartum period. Methods: Dar Al-Shifa Hospital is the largest Ministry of Health hospital in the Gaza Strip, is the referral hospital for the whole area, and includes medical, surgical, and maternity departments. Most women who attend the maternity department (70%) have high-risk pregnancies. The caesarean section rate in 2016 was 27%. 88 midwives and 82 doctors are employed on the maternity wards. We did a descriptive retrospective analysis of all women admitted in labour to the maternity hospital from the start of the Safe Childbirth Project on Sept 1, 2015, to June 30, 2018. Data were extracted from patients' files then aggregated and analysed. Six indicators of quality of care were assessed: risk assessment on admission to the labour ward; use of partograms; oxytocin augmentation of labour; babies delivered by a midwife; breastfeeding initiation within 1 h of birth; and the number of postnatal examinations. Ethics approval was obtained from the Helsinki Committee, at the Palestinian Health Research Council. Findings: Of 16 400 births at Dar Al-Shifa Hospital during the study period, 11 480 (70%) were normal vaginal deliveries. The percentages of women risk assessed on admission increased from 65% at the start of the study to 100% at the end, but the proportions of pregnancies classified as being at low risk or high risk remained at roughly one-third to two-thirds (low risk 20% and high risk 45% at the start of the study vs 30% and 70%, respectively, at the end of the study). Partograms were used in all women throughout the study period. Use of oxytocin augmentation of labour decreased from 24% to 8%. Midwives delivered 53% of low-risk women at the beginning of the study and 100% at the end. The proportion of women who initiated breastfeeding within 1 h of birth increased from 45% to 81% and the percentage of women who had five or more postpartum examinations increased from 27% to 81%. Interpretation: Implementation of the Safe Childbirth Project in Dar Al-Shifa Hospital improved most of our indicators of quality of care and was maintained along with regular clinical auditing. Management commitment and close clinical supervision have been the cornerstones of success. Funding: None.